Results on genetic analysis of pasteurella multocida isolated from local Mongolian cattle (Mongolian Journal of Agricultural Sciences, 2015)
Pasteurella multocida (P. multocida) a small gram-negative coccobacillus, is part of the normal oral flora of many animals, including the pig, bovine, fowl and cat. High morbidity and mortality rates are associated with significant economic losses to the livestock. The aim of this study is to analyze and distinguish phenotypically and genotypically differences between virulent strain isolated from Mongolian cattle and its physically induced mutant strain. For PCR detection, we used specific primers (KMT1T7-FWD, KMT1SP6-R) targeting for kmt1 gene of P. multocida, and specific primers for five serogroups of P. multocida. Nucleotide sequences were analyzed by the Applied Biosystem 3130 xl Genentic Analyzers, using KMT1T7 and KMT1SP6 primers. Completely assembled sequences were aligned with CLUSTAL W and phylogenetic analyses were conducted using MEGA 6.1version.The results of microbiological testing revealed there is no significant importance discrepancy between strains which are P. multocida 18 and P. mutlocida 144. In fermentation studies, P.mutocida18 were using glucose, sucrose, sorbet, mannose, and mannitol, whereas, it didn’t fermentxylose, dulcitol, and raffinose. But P. multocida 144 used fructose, sucrose, sorbet, mannose, mannitol, xylose, and raffinose, whereas it did not use dulcitol. P. multocida detection by standard PCR result was 460 bps specific bands and multiplex-PCR showed 750bpsspecific bands, indicating that ‘B’ serotype of P. multocida. Phylogenetic analysis showed that Mongolian strains and its mutants were very closely correlated each to other by 93%, while other strains including P.multocidaand Pasteurella spp sequences of which were obtained from gene bank were evolutionary related.Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 22-26